Potential Targets for Prevention and Treatment of Nonalcoholic Fatty Liver Disease in Adults: A Review - Jarnail Singh Braich (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Nonalcoholic fatty liver disease (NAFLD) is a prevalent condition that can lead to major liver diseases such as hepatic fibrosis and hepatocellular carcinoma. The most common etiology is a sedentary lifestyle and taking a high-calorie diet. Presently there is no US FDA-approved drug available to treat NAFLD, and only dietary measures, increased physical activity, exercise, antioxidants are the options. In December 2020, the Drug Controller General of India (DGCI) had approved New Drug Application (NDA) for Saroglitazar Mg to treat NAFLD in India. This review describes in detail the pathophysiology, diagnostic methods, and potential targets for NAFLD prevention and treatment.